Music garden : Library as multi gallery / Faculty of Art & Design UiTM Puncak Alam. - Ahmad Sa'id, Alif; Ahmad Razali, Ahmad Afifuddin; Mohd Samingan, Muhammad Raziq (Faculty of Art & Design, Universiti Teknologi MARA Puncak Alam, 2019)
To change the concept of 'information' at UiTM libraries with just book, web-board tools and other. My tea, has come out a new idea is about to create music garden. Music garden is about more relax and more comfortable to study its not just silence study but also can hear a song (with mural of typography, pattern, illustration)